Tes Kecil pada Pembelajaran Kimia di Sekolah Menengah Atas - Nuralia Nuralia; Muntari Muntari; Agus A. Purwoko (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
This study aims to find out the effect of giving recitation tests on learning achievement of senior high school students. One control and two experiment classes were involved, respectively given no test, 6 and 4 recitation tests. Results of variant analysis and t-test indicate that students' learning achievement is greatly influenced by the recitation test, but tes frequency yields no significant difference.